R. M. Flores, The compositors of the first and second Madrid editions of "Don Quixote", Part I. The Modern Humanities Research Association, London, 1975; x + 148 pp. - Rodríguez-Luis, Julio (El Colegio de México, 1977)
Se reseñó el libro: The compositors of the first and second Madrid editions of "Don Quixote", Part I.